2012
DOI: 10.1111/j.1600-0412.2012.01367.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and treatment of rectovaginal endometriosis: an overview

Abstract: Rectovaginal endometriosis can be a cause of severe pain, dyspareunia and intestinal problems. A thorough examination is needed and should include diagnostic imaging, such as transvaginal or transrectal ultrasound or magnetic resonance imaging. Medical therapies, such as oral contraceptives, progestins and levonorgestrel-releasing intrauterine devices, all seem to reduce pain and should always be considered. Surgical treatment is challenging and implies a risk of severe complications. It is preferable to treat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0
12

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 22 publications
(30 citation statements)
references
References 100 publications
0
18
0
12
Order By: Relevance
“…Deep infiltrating endometriosis of the rectovaginal septum is difficult to assess. Evaluating the rectovaginal septum by inspection and palpation requires high expertise [1,2] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Deep infiltrating endometriosis of the rectovaginal septum is difficult to assess. Evaluating the rectovaginal septum by inspection and palpation requires high expertise [1,2] (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…In patients with rectovaginal endometriosis, hormonal therapies decrease the severity of pain , decrease the size of the nodules , and improve quality of life , sexual function and patient satisfaction . In the last few years, several studies have shown that medical therapies (such as norethisterone acetate, low‐dose oral contraceptive pill, triptorelin and letrozole) improve pain and gastrointestinal symptoms of patients with bowel endometriosis and decrease the size of the nodules .…”
Section: Discussionmentioning
confidence: 99%
“…One concerning exception is the postmenopausal patient, in which ovarian cysts with ‘ground glass’ appearance are associated with a 44% risk of malignancy 12. Additionally, TVS may play a role in the evaluation of disease involving the bladder and rectum 14,15…”
Section: Imaging Studiesmentioning
confidence: 99%